2018
DOI: 10.21767/1791-809x.1000568
|View full text |Cite
|
Sign up to set email alerts
|

A Study to Assess the Knowledge, Practice and Attitude on Temporary and Permanent Contraceptive Methods among Primi and Multi Mothers in Selected Areas in Coimbatore

Abstract: A quantitative approach, quasi experimental one group pre-test post-test design aimed to assess the knowledge, practice and attitude on Temporary and Permanent contraceptive methods among primi and multi mother in Alandurai and Rathinapuri areas in Coimbatore, 150 primi and 150 multi mother were selected by non-probability convenient sampling technique was used to assess the knowledge, practice and Attitude by structure questionnaire and reassess the know ledge, practice and attitude. There was a significant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Another study also showed male condom to be the preferred method whereas all the other studies showed oral contraceptive pills to be the preferred method. 9,13,14 These findings suggest a positive effect of counselling on acceptance of contraceptive methods and a greater need to spread awareness by media and repeated counselling on an individual basis. The three main reasons for accepting a particular method of contraception were found to be the ease of availability, ease of use and fewer side effects.…”
Section: Resultsmentioning
confidence: 97%
“…Another study also showed male condom to be the preferred method whereas all the other studies showed oral contraceptive pills to be the preferred method. 9,13,14 These findings suggest a positive effect of counselling on acceptance of contraceptive methods and a greater need to spread awareness by media and repeated counselling on an individual basis. The three main reasons for accepting a particular method of contraception were found to be the ease of availability, ease of use and fewer side effects.…”
Section: Resultsmentioning
confidence: 97%
“…methods which has been contributed to either ignorance or fear of its complication. 8 The United Nations Population Fund (UNFPA) reported that in Tanzania, the contraceptive prevalence rate (CPR) for modern methods among currently married women (aged 15-49) is 32%. In addition, the unmet need for family planning for currently married women aged 15 to 49 is 22%.…”
Section: Introductionmentioning
confidence: 99%
“…Though, contraception availability has been widely scaled up, there is poor acceptance of contraception͘ methods which has been contributed to either ignorance or fear of its complication. 8 The United Nations Population Fund (UNFPA) reported that in Tanzania, the contraceptive BACKGROUND F amily planning refers to a conscious effort by a couple to limit or space the number of children through the use of contraceptive methods. 1 It is a voluntary adapted way of living and thinking by the couples based on their knowledge, attitude and responsible decisions.…”
mentioning
confidence: 99%